A nun for the viking warrior - Morris, Lucy (Romance fiction writer) (Harlequin historicals., 2021)
Noblewoman Amée Évreux had pledged her life to God, until her father promised her in marriage to thundering Norseman Jorund Jötunnson. After escaping her overbearing father, Amée vows never to fall under another man's thumb, but her resistance to being Jorund's wife turns to desire as she gets to know her intriguing new husband. For beneath his fierce exterior she's glimpsed an unexpectedly pure heart. If only she can penetrate the fortress that surrounds it.